LITERATURE REVIEW ON DIGITAL LITERACY: BUILDING BASIC COMPETENCE AMONG STUDENTS IN DEVELOPING COUNTRIES - Welsi Damayanti; Nur Rahmad Yahya Wijaya; Rasuki (Indonesian Journal of Education (INJOE), 2025)
This study aims to analyse digital literacy and efforts to build basic competencies among learners in developing countries. Digital literacy includes the technical ability to use digital devices and applications, as well as critical skills in evaluating information and understanding the ethical implications of technology. While access to information and communication technologies has increased, many learners in developing countries still lack adequate digital literacy skills. Factors such as limited infrastructure, inequality of educational resources and low levels of teacher training are significant barriers. Literature studies show that a holistic approach that incorporates technical, critical and ethical aspects is essential in developing digital literacy. Digital literacy should be integrated into the education curriculum systematically and supported by adequate training for educators. In addition, collaboration between the government, educational institutions, non-governmental organisations and the private sector is needed to create an ecosystem that supports the development of digital literacy. Thus, there is a need for coordinated policies and initiatives to improve digital literacy among learners in developing countries. Investments in technology infrastructure, training programmes and the provision of quality educational resources are key to preparing young people for the challenges and opportunities of the digital age. With adequate digital literacy, learners in developing countries can more effectively contribute to the economic and social development of their communities.